Prospects for the Development of Smart Clothing with the Use of Textile Materials with Magnetic Properties - Mykola Riabchykov; Alexandr Alexandrov; Roman Trishch; Anastasiia Nikulina; Natalia Korolyova (Tekstilec, 2022)
The article studies the properties of textile materials filled with magnetite nanoparticles. These materials have great prospects for creating smart clothes. They have both magnetic and hygienic properties. Chemical transformations in the production of magnetic nanopowder are described. The end product of the process is a mixture of oxides of divalent and ferric iron. The resulting mixture has magnetic properties. Conducted micro and macro experiments showed sufficient adhesion retention strength of magnetite nanoparticles in a textile material. Microscopic studies of the attachment of magnetic particles to the fibers of a textile material have been conducted. The data obtained in express mode allow us to determine the average mass of a magnetic particle in a textile material, the total number of nanoparticles, and, accordingly, to predict the magnetic force that a textile material saturated with magnetite can possess. The existence of the magnetic properties of a textile material filled with magnetite nanoparticles has been proven. A mathematical model of the dependence of the magnetic attraction force of a textile material on the distance and the number of abrasion cycles has been developed. The directions of the use of magnetic textile materials for the creation of smart clothes are proposed. Potential uses for such materials include sportswear and textiles for the disabled. The developed methods can predict the magnetic strength of the obtained textile materials and evaluate their resistance, which is necessary in the development of smart clothing elements based on these materials.